View on the Iraqi political map after the last election (March 7) (Journal of the College of Basic Education, 2022)
Explosions in the Baghdad downtown broke out on April 4 and 6, right at the time when four winning coalitions leaders in the Iraqi parliamentary elections were starting consultations on future prime minister position holder. However, one may say people have accustomed to terrorist attacks. If it’s possible to get accustomed to such bloody incidents